The scientometric evaluation of the institutional research: The Marmara Universities- Part 1 - Konur, Özcan (SILA SCIENCE, 2013)
The scientometric analysis of the research has become one of the most used methods to assess the research performance of the scholars, departments, faculties, universities, countries, and journals in recent years. However, there has not been an extensive scientometric evaluation of the institutional research carried out by the universities in the Marmara Region of Turkey, a most developed region of Turkey, to examine the development of the research over time. Hence, the purpose of this study was to carry out a scientometric evaluation of the research performed by these universities using three indices in a series of four papers. In the first part of these serial papers, it was found that there were 58 universities founded between 1933 and 2011 in 11 cities including Istanbul and there were 13,953 senior members of the academic staff in these universities, comprising 31% of the national academic force. 39 (67.3%) and 19 (32.7%) of these universities were state and foundation universities, respectively. Four, four, twenty, fifteen, and fifteen of these universities were pre-1980, 1980, 1990, 2000, and 2010 universities, respectively. 35.2% of the regional academic force was employed by the pre-1980 universities whilst 19.3%, 36.9%, and 8.3% of them were affiliated with the 1980, 1990, and 2000 universities, respectively. Only three of the 2010 universities had academic staff entry as of November 2010. Istanbul University was the first established university of the region, founded in Istanbul in 1933. As a state university, it had 2,650 academic staff comprising 19.0% of the regional academic force. The top university in terms of the number of the academic staff was Istanbul University, followed by Marmara University, Istanbul Technical University, Uludag University, and Sakarya University. The foundation universities in general did not follow a heavy expansion strategy whilst most state universities did with a few exceptions. Istanbul had 45 universities whilst Bursa and Kocaeli had 3 and 2 universities, respectively. The results found in the first part suggest that there was a close structure-research performance relationships for these universities as there were huge range of structural differences among the regional universities hinting the strong effect of the formal and informal rules adapted by these universities on their respective research productivity following North's new institutional theoretical framework.
Keywords: AandHCI; SSCI; SCIE; Marmara Universities; Web of Knowledge; Turkey; Incentive structures; Research evaluation geography; Research productivity; Scientometrics